X-Ray reduction imaging of inclined reflective masks at critical angles. (September 2016) - Artyukov, I.A.; Busarov, A.S.; Vinogradov, A.V.; Popov, N.L.
Abstract: We have proposed and simulated optical schemes for producing reduced images by X-ray lasers or harmonic generators at a wavelength of . The mask in this case is placed at a small angle to the optical axis, corresponding to the angle of total external reflection of the material. We have determined the optimal position of the detector (resist) and the corresponding spatial resolution. The results can be used to solve problems in nanotechnology and nanostructuring of surfaces.